Generation of reticulocytes derived from human umbilical cord blood cd34- haematopoietic stem cells for plasmodium knowlesi ln vitro culture - Maketar, Solihah (2020)
The emergence of zoonotic malaria parasite, P. knowlesi becomes the most dominant parasite causing malaria infection in humans in the Southeast Asia where Malaysian Borneo has recorded to have the highest cases of malaria diseases caused by P. knowlesi. It has been reported that P. knowlesi shows preference towards reticulocytes. However, obtaining a huge amount of reticulocytes for the continuous supply becomes the major hurdle for a long-term culture study. This is due to the low concentration of reticulocytes circulating in peripheral blood, bone marrow and umbilical cord blood. Fortunately, the development system in in vitro culture to generate reticulocytes derived from haematopoietic stem cells (HSCs) could solve the limitation of the P. knowlesi study. In this study, umbilical cord blood (UCB) was used as the source of HSCs which contained the highest concentration of CD34+ compared to peripheral blood and bone marrow. First, UCB-derived CD34+ HSCs were expanded in serum-free expansion medium II (SFEM) supplement with cytokines allowing the cells to proliferate. After 5 days of expansion, the cells were cultured in differentiation media with sufficient growth factors and cytokines for the process of reticulocytes differentiation. Microscopic examination and FACS analysis were performed during the cultivation period to observe the morphological changes and monitor the expression of cell surface antigens. Lastly, P. knowlesi was cultured in the generated reticulocytes and the invasion rate was determined at 24-hour post-invasion. Although the invasion of P. knowlesi was not performed due to unforeseen circumstances, the result showed that functional reticulocytes could be generated from UCB-derived CD34+ HSCs and the invasion rate of P. knowlesi was expected to be similar with P. vivax. This is because P. knowlesi has the closest phylogenetically with P. vivax. In conclusion, this study shows the possibility to produce massive production and homogenous populations of reticulocytes generated from UCB-derived CD34+ HSCs.